Isolasi Katekin dari Teh Hijau (Camellia sinensis) Menoreh Berbasis Gelombang Mikro serta Evaluasi Efektivitas Antibakterinya - Marwanto, Ari Tri; Ma'mun, Sholeh; Mukti, Nur Indah Fajar (Chemistry Department, Universitas Islam Indonesia, 2026)
Green tea (Camellia sinensis) is a rich source of bioactive compounds such as catechins, tannins, caffeine, and flavonoids, with catechins known for their antibacterial activity; however, their extraction yield remains relatively low, necessitating optimization. This study investigated the effects of temperature (40 – 60 °C) and extraction time (3 – 9 minutes) using Microwave-Assisted Extraction (MAE) on catechin yield, as well as the antibacterial activity against Staphylococcus aureus, Streptococcus mutans, and Pseudomonas aeruginosa. A total of 5 g of dried green tea powder was extracted with 50 g of 60% ethanol at a microwave power of 450 W, followed by solvent evaporation and catechin analysis using High Performance Liquid Chromatography (HPLC). The results showed that the yield increased with higher temperature and longer extraction time, reaching a maximum of 4.98% at 60 °C for 9 minutes. The disc diffusion assay revealed the largest inhibition zone against P. aeruginosa (19.67 mm), followed by S. aureus (17.50 mm) and S. mutans (12.50 mm). The Minimum Inhibitory Concentration (MIC) was 3.125% and the Minimum Bactericidal Concentration (MBC) was 6.25% (MBC/MIC ≤ 4), indicating bactericidal activity. These findings confirm that MAE optimization effectively enhances catechin yield while producing extracts with promising potential as natural antibacterial agents.